Studi Tafsir Tematik Atas Kisah Musa Dan Harun: Implikasi Terhadap Paradigma Dakwah Kolaboratif - Hidayatulloh, Jajang; Rustandi, Ridwan (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This study examines the story of Prophet Musa and Prophet Harun ‘alayhimā as-salām in the Qur'an using a thematic exegesis (tafsīr maudhū‘ī) approach, focusing on its implications for the paradigm of collaborative da'wah in Islam. Prophetic missions often face significant challenges, both external—such as societal rejection—and internal, including individual limitations. In this context, the Qur'an presents the complementary roles of Musa as the primary leader and Harun as his supportive companion. Relevant verses such as Sūrat Ṭāhā [20]: 29–36 and Sūrat al-Qaṣaṣ [28]: 34 reveal that Musa’s request for Harun’s companionship had strategic and theological grounds. This study highlights that their collaboration was not merely supplementary but rather an integral element of the da'wah’s success. Through the analysis of classical and contemporary tafsīr literature, the research finds that synergy, mutual support, and clear role distribution are essential principles in effective collaborative da'wah. The findings of this research aim to enrich contemporary Islamic da'wah discourse by offering a prophetic model of cooperation that remains relevant and applicable amid modern challenges.